Influence of paste thickness on coated aggregates on properties of high-density sulphoaluminate cement concrete. (15th July 2016) - Sun, Keke; Zhou, Xiangming; Gong, Chenchen; Ding, Yanyu; Lu, Lingchao
Highlights: High-density sulphoaluminate cement concrete is prepared with improved DMAD. The shape of aggregates is assumed square and spherical to calculate paste amount. Effect of paste thickness on the properties of HDSC was studied. Abstract: An improved method for the densified mixture design algorithm and Fuller curve were used to design high-density sulphoaluminate cement concrete (HDSC). The performance of HDSC is significantly influenced by the paste thickness on the coated aggregates. Sulphoaluminate cement concrete mixtures containing aggregates coated with 3 different paste thickness of t = 10 μm, 20 μm, and 30 μm and water-binder ratios of 0.25, 0.30 and 0.35 were prepared. The results of experiments show that paste thickness on the coated aggregates significantly influences the mechanical properties and durability of HDSC. With the increase of paste thickness, the compressive strength is increased, but the electrical resistivity is decreased, particularly at the early ages of 1 and 3 days. The sulfate corrosion resistance coefficients of HDSC are larger than 1.0, the total porosity can be less than 7%, and the micropore (i.e. with pore size less than 20 nm) can be larger than 70%.